Short Communication Correlation and Regression Coefficient Estimates between some Growth Performance Traits of Harnai Sheep (Biological Sciences - PJSIR, 2018)
Present investigation was carried out to estimate the correlation and regression coefficientestimates between some growth performance traits of Harnai sheep. The available data was collected andmaintained at Multipurpose Sheep Research Centre Yetabad, District Loralia, Balochistan, Pakistan. Thedata regarding growth traits including birth weight, yearling weight, weaning weight and fleeces weightwas analysed for the estimation of correlation and regression coefficient. In present study the results forcorrelation and regression coefficient estimates were observed low to positive between some growthperformance traits of Harnai sheep. Due to low results for correlation and regression coefficient, it isconcluded that mass selection is advisable for achieving better performance in growth traits of Harnaisheep.